2010
DOI: 10.1002/emmm.201000106
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial FAK is required for tumour angiogenesis

Abstract: Focal adhesion kinase (FAK) is a cytoplasmic tyrosine kinase that plays a fundamental role in integrin and growth factor mediated signalling and is an important player in cell migration and proliferation, processes vital for angiogenesis. However, the role of FAK in adult pathological angiogenesis is unknown. We have generated endothelial-specific tamoxifen-inducible FAK knockout mice by crossing FAK-floxed (FAKfl/fl) mice with the platelet derived growth factor b (Pdgfb)-iCreER mice. Tamoxifen-treatment of Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 46 publications
8
112
1
Order By: Relevance
“…[26][27][28] Recently, we reported that NDNF enhances the phosphorylation of Akt and its downstream molecule eNOS, and capillary formation in ischemic skeletal muscle of mice. 5 We also demonstrated that NDNF promotes network formation of endothelial cells through its ability to stimulate the phosphorylation of Akt and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Recently, we reported that NDNF enhances the phosphorylation of Akt and its downstream molecule eNOS, and capillary formation in ischemic skeletal muscle of mice. 5 We also demonstrated that NDNF promotes network formation of endothelial cells through its ability to stimulate the phosphorylation of Akt and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, leads to increased (18,19). In addition, FAK-induced cell migration has been associated with the development of various neoplasms (2,20). Thus, the blocking of FAK is a plausible target for therapeutic inhibition of cell motility, and perhaps of angiogenesis, since endothelial cell migration is crucial during the angiogenic process.…”
Section: Effects Of Pf573228mentioning
confidence: 99%
“…Focal adhesion kinase is required for tumor angiogenesis (20,21). Therefore, FAK may be an important target in the abrogation of tumor angiogenesis, especially in the context of problematic vascular tumors such as infantile hemangiomas (IH) and hemangioendotheliomas.…”
Section: Effects Of Pf573228mentioning
confidence: 99%
“…In both settings it is apparent that endothelial FAK is an important mediator of VEGF-induced neovascularization. 20,21 Taken together, these findings provide strong rationale for targeting FAK to simultaneously counter tumor metastasis and angiogenesis. To this end, there has been a surge in the discovery and preclinical development of agents directed against FAK.…”
Section: Discussionmentioning
confidence: 85%
“…20,21 To explore the relationship between ovarian cancer cell FAK and pFAK expression and the tumor vasculature, we stained the specimens for CD31 and quantified microvessel density (MVD). The median MVD was 21.6 vessels/high power field (range, 8.6-38.3 vessels/high power field).…”
Section: Y397 Expression To Angiogenesismentioning
confidence: 99%